Aplicación de la estrategia de aprendizaje basada en el método de solución de problemas para mejorar la capacidad de razonamiento matemático en los estudiantes del primer grado de educación secundaria de la institución educativa “Jesús Nazareno” Chocope, 2 007 - Bazán Cobeñas, Nélida (2012)
The intention of the investigation it was to determine the influence of the strategy of leamings, based on the method of solution of problems, in the improvement of the capacity of mathematical reasoning of the students of the first degree of Secondary Education of the Educational Institution “Jesus Nazareno” of Chocope, in 2007. This investigation is of experimental type and inside this one the Quasiexperimental one, with groups I experiment and control, having as population target 79 students of the first the degree of Secondary Education, with an average age 12 years, distributed in three sections “A”, ”B” and “C”. At random one determined that the section “C” is the experimental group and the section “B” the group control, with a sample of 53 students, 27of the experimental group and 26 of the group control likewise, they were in use as instruments of I gather from information the test whose results were treated statistically. Since corollary can steady that there was increased significantly the capacity of mathematical reasoning of the students of the first degree of Secondary Education, since it is demonstrated by the comparative analysis of the results of the Pretest and Postest , of the groups experimentally and of control, and that the above mentioned increase owes to itself to the application of the leaming strategy, based of the method of solution of problems, which emphasizes his importance in the process education-leaming of the students.